Long‐Range Ordered Crystals of 3D Inorganic–Organic Heterojunctions via Colloidal Lithography. Issue 10 (11th June 2019) - Kandjani, Ahmad Esmaielzadeh; Ramanathan, Rajesh; Zabara, Mahsa; Sabri, Ylias M.; Bhargava, Suresh K.; Bansal, Vipul
Abstract: Colloidal lithography (CL) has evolved as an alternative to conventional photo‐ and electron‐beam lithography to pattern surfaces with nanometer range resolution. As CL offers substrate‐independent precise positioning and patterning of nanomaterials as long‐range ordered crystals, this has seen new opportunities in optoelectronics. Herein, the scope of CL is expanded to fabricate for the first time, 3D organic–inorganic heterojunction photocatalysts with well‐controlled spacing and coverage density. To achieve this, monodisperse polystyrene (PS) beads of different sizes are used as colloidal masks on a ZnO substrate. Electron beam assisted silver deposition onto these PS masks, and subsequent removal of PS lead to the formation of patterns of silver nanostars on the ZnO thin film. The solid–vapor reaction of silver nanostars with a metal‐coordinating charge‐transfer complex of 7, 7, 8, 8‐tetracyanoquinodimethane (TCNQ) allows spontaneous conversion of Ag nanostars to the large aspect ratio nanowires of metal–organic AgTCNQ semiconductors. This strategy, combining the strengths of CL with high electron affinity of TCNQ molecules allows facile fabrication of long‐range patterns of the heterojunctions of organic (AgTCNQ) and inorganic (ZnO) semiconductors. These surface‐supported 3D heterojunctions act as outstanding photocatalysts through their ability to efficiently separate the electron–hole pairs and thus increasing the electron–hole life times. Abstract : A facile and reproducible method to produce patterned surfaces of organic/inorganic semiconductor heterojunctions of ZnO/Ag/AgTCNQ is reported. A precise control over the position, coverage, and size of inorganic/organic heterojunctions using a nonconventional colloidal lithography approach is shown. These heterojunction surfaces show outstanding photocatalytic activity.